کلتوورى کوردو ڕێککەوتنامەى سایکس - بیکۆ - صالح, عزت فتاح حمه‌ (Sulaimani Journal for Humanities, 2018)
Kurdish culture and the Sykes-Picot agreement The research shows historical agreement which was affected of Kurdish culture, this was a secret agreement between the governments of the United Kingdom and the French in 1916, with the assent of the Russian empire during the World war1. It was about dividing Iraq(Sham) and Middle East after succeed in defeating the Ottoman Empire, which was sing between British Mark Sykes and Francois Georges-Picot to dividing this areas. So Britain was allocated control areas (Mediterranean Sea and River Jordan, Jordan and southern Iraq) and France was allocated control areas (Turkey, Syria, northern Iraq and Lebanon) but Palestine into areas of future British and France control and influences with the right to use the ports of Haifa, Acre and Mediterranean. Furthermore, Russian was received Istanbul, the Turkish Straits, Armenia and Kurdistan from this agreement. But the October revolution in 1917 affected Russia to reject the agreement and publishedother secret agreements which were exit between Russian and Britain in 1907. This agreements surly effect the Kurdish culture which causes to make the weakness and changein Kurdish culture and some has been lost because of the central government culture that controls Kurdish areas, this let to meltKurdish cultures because of culture superiority. Briefly the Sykes-Picot agreement brings a lot of advantages to neighbourgovernments which have got Kurdish areas. However, brings a lot of disadvantages to Kurdistan such as war, conflict and economiccrisis, more importantly causes to dividing Kurdish cultures, with barriers for having Kurdish state for a century.